Experience with peroneus brevis muscle flaps for reconstruction of distal leg and ankle defects - Babu Bajantri; Ravindra Bharathi; Sanjai Ramkumar; Latheesh Latheef; Smitha Dhane; S. Raja Sabapathy (Indian Journal of Plastic Surgery)
Objective: Peroneus brevis is a muscle in the leg which is expendable without much functional deficit. The objective of this study was to find out its usefulness in coverage of the defects of the lower leg and ankle. Patients and Methods: A retrospective analysis of the use of 39 pedicled peroneus brevis muscle flaps used for coverage of defects of the lower leg and ankle between November 2010 and December 2012 was carried out. The flaps were proximally based for defects of the lower third of the leg in 12 patients and distally based for reconstruction of defects of the ankle in 26 patients, with one patient having flaps on both ankles. Results: Partial flap loss in critical areas was found in four patients requiring further flap cover and in non-critical areas in two patients, which were managed with a skin graft. Three of the four critical losses occurred when we used it for covering defects over the medial malleolus. There was no complete flap loss in any of the patients. Conclusion: This flap has a unique vascular pattern and fails to fit into the classification of the vasculature of muscles by Mathes and Nahai. The unusual feature is an axial vessel system running down the deep aspect of the muscle and linking the perforators from the peroneal artery and anterior tibial artery, which allows it to be raised proximally or distally on a single perforator. The flap is simple to raise and safe for the reconstruction of small-to moderate-sized skin defects of the distal third of the tibia and all parts of the ankle except the medial malleolus, which is too far from the pedicle of the distally based flap. The donor site can be closed primarily to provide a linear scar. The muscle flap thins with time to provide a good result aesthetically at the primary defect.